Structural Insights into Hysteretic Spin‐Crossover in a Set of Iron(II)‐2, 6‐bis(1H‐Pyrazol‐1‐yl)Pyridine) Complexes. Issue 6 (19th January 2022) - Suryadevara, Nithin; Mizuno, Asato; Spieker, Lea; Salamon, Soma; Sleziona, Stephan; Maas, André; Pollmann, Erik; Heinrich, Benoît; Schleberger, Marika; Wende, Heiko; Kuppusamy, Senthil Kumar; Ruben, Mario
Abstract: Bistable spin‐crossover (SCO) complexes that undergo abrupt and hysteretic (Δ T 1/2 ) spin‐state switching are desirable for molecule‐based switching and memory applications. In this study, we report on structural facets governing hysteretic SCO in a set of iron(II)‐2, 6‐bis(1 H ‐pyrazol‐1‐yl)pyridine) (bpp) complexes – [Fe(bpp−COOEt)2 ](X)2 ⋅ CH3 NO2 (X=ClO4, 1 ; X=BF4, 2 ). Stable spin‐state switching – T 1/2 =288 K; Δ T 1/2 =62 K – is observed for 1, whereas 2 undergoes above‐room‐temperature lattice‐solvent content‐dependent SCO – T 1/2 =331 K; Δ T 1/2 =43 K. Variable‐temperature single‐crystal X‐ray diffraction studies of the complexes revealed pronounced molecular reorganizations – from the Jahn‐Teller‐distorted HS state to the less distorted LS state – and conformation switching of the ethyl group of the COOEt substituent upon SCO. Consequently, we propose that the large structural reorganizations rendered SCO hysteretic in 1 and 2 . Such insights shedding light on the molecular origin of thermal hysteresis might enable the design of technologically relevant molecule‐based switching and memory elements. Abstract : Jahn‐Teller distortion and substituent conformational switching – mediated hysteretic spin‐state switching is reported for two mononuclear iron(II)‐2, 6‐bis(1 H ‐pyrazol‐1‐yl)pyridine) (bpp) complexes. Stable hysteretic switching of Δ T 1/2 =62 K and Δ T =288 K is observed for one of the complexes: Fe[(bpp−COOEt)2 ](ClO4 )2 ⋅ CH3 NO2 . This complex is unprecedented for the iron(II)−bpp family and encourages the pursuit of iron(II)‐based SCO complexes for molecule‐based switching and memory applications.